The Effect of Different Mixing Methods on the Flow Rate and Compressive Strength of Mineral Trioxide Aggregate and Calcium-Enriched Mixture - Shahi, Shahriar; Ghasemi, Negin; Rahimi, Saeed; Yavari, Hamid Reza; Samiei, Mohammad; Janani, Maryam; Bahari, Mahmood; Moheb, Sanaz (Iranian Endodontic Journal, 2014)
Introduction: Flow rate (FR) and compressive strength (CS) are important properties of endodontic biomaterials that may be affected by various mixing methods. The aim of this experimental study was to evaluate the effect of different mixing methods on these properties of mineral trioxide aggregate (MTA) and calcium-enriched mixture (CEM) cement. Materials and methods: Hand, amalgamator and ultrasonic techniques were used to mix both biomaterials. Then 0.5 mL of each mixture was placed on a glass slab to measure FR. The second glass slab (100 g) was placed on the samples and 180 sec after the initiation of mixing a 100-g force was applied on it for 10 min. After 10 min, the load was removed, and the minimum and maximum diameters of the sample disks were measured. To measure the CS, 6 sample of each group were placed in steel molds and were then stored in distilled water for 21 h and 21 days. Afterwards, the CS test was performed. Data were analyzed with multi-variant ANOVA and post hoc Tukey tests. The level of significance was set at 0.05. Results: There were significant differences in FR of MTA and CEM cement with different mixing techniques (P<0.05). In the MTA group, none of the mixing techniques exhibited a significant effect on CS (P>0.05); however, in CEM group the CS at 21-h and 21-day intervals was higher with the hand technique (P<0.05). Conclusion: Mixing methods affected the flowability of both biomaterials and compressive strength of CEM cement.